Compassionate love in intimate relationships : the integration process of sexual mass trauma, racism, and resilience - Apollon, Josiane M. (New York, NY : Routledge, 2022)
"Drawing on interviews conducted with Black couples in the US, this book explores relational resilience and identifies unique adaptation strategies that enable couples to overcome the multigenerational effects of violence and sexual mass trauma from slavery and activates compassionate love in flourishing relationships. By applying Appreciative Inquiry (AI) methodology and family systems theory, the book captures the spiritual, emotional, and sexual dimensions in black couple systems that gives meaning to their resilient relationships in the context of contemporary America. Within the framework of compassionate love, the book highlights the need for researchers and clinicians to include the broader cultural contexts in their sexual trauma-informed studies and interventions. Using genetic studies and empirical evidence, the volume contributes significantly to discussion around Black relationships and historical trauma, and to the broader challenges within race relations in the United States. This book will benefit researchers, academicians, and clinicians with an interest in sexual trauma, marriage and family therapy, and couples counseling more broadly. Readers will also find this book useful when designing research in Black studies, intergenerational issues, or sexual intimacy. Josiane M. Apollon completed her PhD Nova Southeastern University's Family Therapy Doctoral program and has been a Licensed Mental Health Counselor for over 20 years, serving multicultural clients in the US and abroad. She is the Clinical Director at Integrative Wellness, specializing in couples and family therapy"--
Introduction: A Path to Human Integration -- The Historical Context of Humanity and Sexual Mass Trauma -- The Cultural Context of the American Slavery System -- Appreciative Inquiry Methodology and Systems Theory with Couples -- Analysis of Couple Systems: The Integration of Spirituality, Compassionate -- Love, and Sexuality -- Implications for Future Couple Research and Clinical Practice.
Keywords: African Americans -- Psychology; African American couples -- Psychology; Intimacy (Psychology); Sex (Psychology); Compassion; Interpersonal relations; Racism -- United States -- Psychological aspects; United States -- Race relations -- Psychological aspects; PSYCHOLOGY / Psychotherapy / Couples & Family; PSYCHOLOGY / Research & Methodology